Transforming Health Insurance Law: Toward Substantive Justice for Health Social Security Administering Body - Deborah Johana Rattu; T subarsah (Universitas Muhammadiyah Sumatera Utara, 2026)
Health is a fundamental right guaranteed under Article 28H of the 1945 Constitution of the Republic of Indonesia, obligating the state to provide inclusive and equitable access to healthcare services. The establishment of the National Health Insurance (NHI) Program, administered by the Social Security Administrative Body for Health (SSAB-Health), marked a significant milestone in the transformation of Indonesia’s health insurance system. However, despite its normative foundation in constitutional and statutory law, the program faces persistent challenges in practice, including discrepancies between contribution adjustments and service quality, regional disparities in healthcare infrastructure, delayed claim reimbursements, discriminatory practices against participants, and limited public understanding of rights and obligations. This study analyzes these problems using legal and governance theories, including the distinction between formal and substantive justice, spatial justice, legal culture, and good governance principles. The findings demonstrate that while the NHI Program has expanded coverage, its effectiveness is weakened by systemic inequities and governance deficiencies that undermine its legitimacy and protective function. The paper argues for a comprehensive legal transformation that emphasizes substantive justice, encompassing regulatory reforms, institutional restructuring, stronger protection of patient rights, infrastructure capacity building, and enhanced public education. Such transformation is essential not only to fulfill constitutional mandates but also to contribute to broader national development objectives, including poverty reduction, human capital enhancement, and social cohesion. In this way, the reformation of health insurance governance serves as both a legal imperative and a strategic pathway toward achieving social justice in Indonesia.